2010
DOI: 10.1088/0253-6102/54/3/33
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermodynamics of Liquid Noble-Metals Alloys Through a Pseudopotential Theory

Abstract: On the bases of the Gibbs-Bogoliubov (GB) inequality and the Percus-Yevick (PY) hard sphere model as a reference system, a thermodynamic perturbation method has been applied with use of well recognized model potential. By applying a variation method the best hard core diameters have been found which correspond to minimum free energy. With this procedure the thermodynamic properties such as entropy and heat of mixing have been computed. The influence of local field correction function viz; Hartree (H), Taylor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The hard sphere reference system estimates the more promising value of excess entropy Sexs than the other system. Present results also follow the same fashion for this estimation for PYHS [3][4][5][6][7][8][9][10][11] reference system instead just as HS reference system. As compared to the Sexs by OCP reference system given in the article of Dubinin et al [1], the Sexs calculated in the HS reference system is found higher.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The hard sphere reference system estimates the more promising value of excess entropy Sexs than the other system. Present results also follow the same fashion for this estimation for PYHS [3][4][5][6][7][8][9][10][11] reference system instead just as HS reference system. As compared to the Sexs by OCP reference system given in the article of Dubinin et al [1], the Sexs calculated in the HS reference system is found higher.…”
Section: Resultssupporting
confidence: 75%
“…The Gibbs-Bogoliubov (GB) approximation has been found an appropriate tool to study the thermodynamics of liquids metals [1][2][3][4][5][6][7][8][9][10][11]. According to it, the Helmholtz free energy can be written as,…”
Section: Computational Methodologymentioning
confidence: 99%
See 3 more Smart Citations